Current instabilities in resonant tunnelling diodes based on GaN/AlN heterojunctions - Belyaev, A.E.; Foxon, C.T.; Novikov, S.V.; Makarovsky, O.; Eaves, L.; Kappers, M.J.; Barnard, J.S.; Humphreys, C.J.; Danylyuk, S.V.; Vitusevich, S.A.; Naumov, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Present paper studies double barrier resonant tunnelling diodes (DB-RTD) based on GaN/AlGaN heterostructures, grown by plasma-assisted molecular beam epitaxy (PA-MBE). Tunnel (current-voltage, I–V) and capacitance (capacitance-voltage, C–V) spectroscopy measurements were performed at the temperature range from 4.2 to 300 K. It has been found that measured characteristics of DB-RTD have complex nonlinear behavior and reveal the current discontinuities of I–V curves. The features can be explained by the existence of polarization fields and interface defects. These effects strongly influence on the potential profile of the DB-RTD heterostructures. To understand physics of the processes, numerical simulations of the given structures, using a model based on real-time Green’s functions, have been performed. Comparative analysis of experimental and numerical data showed that the current instability and nonlinearity of characteristics of the nitride based DB-RTD can be connected with trapping the electrons onto interfacial and dislocation states in these heterostructures.